Vagus Nerve Stimulation Paired With Rehabilitation in the Home Environment for People With Chronic Post-Stroke Upper Limb Deficits (VNS-REHAB At-Home): Protocol for a Feasibility Trial. - Doherty, Shannon J.; Patel, Ruchi; Spinelli-Guglielmo, Lisa; Zera, Sarah M.; Antares, Kathleen A.; Diedrich, Annie; Adham Hinds, Reema; Engineer, Navzer D.; Prudente, Cecília N. (Advances in Rehabilitation Science & Practice, 2025)
Background and Rationale: Paired vagus nerve stimulation (VNS) has emerged as a safe and effective therapy to reduce upper limb (UL) motor deficits and improve motor function in individuals with chronic ischemic stroke with moderate-to-severe arm impairment. VNS paired with rehabilitation motor tasks led by an occupational or physical therapist is typically done in-clinic during initial treatment. Attending regular outpatient sessions can be difficult for individuals with limited mobility/transportation. Objectives: The primary objective of the VNS-REHAB At-Home study is to assess the feasibility, safety, compliance, and therapist/patient acceptance of delivering up to 36 hours of therapist-activated VNS paired with UL rehabilitation in a home setting. Secondary objectives include evaluating improvements in UL impairment and function. Trial Design: The acute stage is therapist-activated VNS therapy paired with at home rehabilitation in 1- to 2-hour sessions up to 5 times per week for up to 18 weeks, with a maximum of 36 total hours of therapist visit duration. The long-term stage is a follow-up period of up to 2 years during which participants continue self-activated VNS at home using a magnet during functional tasks. Study Setting: Therapist-activated Paired VNS will be done in the participant's home. Eligibility Criteria: Participants implanted or scheduled to be implanted commercially with the Vivistim Paired VNS System and assessed as able to receive therapist-activated VNS in the home setting. Interventions: The study will use mobile therapists in the participant's home instead of a clinic for the initial treatment phase. Paired VNS will be done according to the manufacturer's instructions for use. Outcomes: The primary endpoint is the number of individuals who complete at least 24 hours of therapy provided in the home setting by a therapist within an 18-week period. Secondary endpoints are change from baseline in assessment measures and patient-reported outcomes. Sample Size: Up to 150 participants.